Delta X : der Kurator als Katalysator. - Acconci, Vito; Babias, Marius; Bronfen, Elisabeth; Christov-Bakargiev, Carolyn; Fischer, Judith; Fleck, Robert; Golub, Leon; Gonzalez-Torres, Felix; Gordon, Douglas; Halperin, Joan U.; Hopps, Walter; Hyber, Fabrice; et al. (Regensburg : Lindinger + Schmid Verlag GdbR, 1996)
Fischli & Weiss ; Boltanski, Christian ; Feldmann, Hans-Peter ; Miller, John ; Hopps, Walter ; Wentworth, Richard ; Virilio, Paul ; Richter, Gerhard ; Tiravanija, Rirkrit ; Absalon ; Boetti, Alighiero ; Gonzalez-Torres, Felix ; Guilleminot, Marie-Ange ; Eichhorn, Maria ; Slominski, Andreas ; Grigely, Joseph ; Orozco, Gabriel ; Hoffmann, Leni ; Gette, Paul-Armand ; Hyber, Fabrice ; Kabakov, Ilya ; Kelley, Mike ; Knowles, Alison ; Koo Jeong-a ; Lavier, Bertrand ; Pistoletto, Michelangelo ; Wurm, Erwin ; Hirst, Damien ; Ono, Yoko ; Fleck, Robert ; Gilbert & George ; Gordon, Douglas ; Latham, John ; Molacek, Ruth ; Zittel, Andrea ; Trockel, Rosemarie ; Acconci, Vito ; Sterling, Bruce ; Obholzer, Walter ; Golub, Leon ; Spero, Nancy ; Kim, Soo-Ja ; Rockenschaub, Gerwald
boek